2012
DOI: 10.1080/14786419.2011.643885
|View full text |Cite
|
Sign up to set email alerts
|

In vitroevaluation of the anti-proliferative activities of the wood essential oils of threeCedrusspecies against K562 human chronic myelogenous leukaemia cells

Abstract: There are four kinds of Cedar: Cedrus libani naturally occurring in Lebanon, Syria and Turkey, Cedrus atlantica in Morocco and Algeria, Cedrus brevefolia in Cyprus Island and Cedrus deodara which is distributed in Himalayan Mountains. Wood essential oils obtained from C. libani, C. atlantica and C. deodara were tested for the inhibition of K562 cell proliferation and for the induction of erythroid differentiation. The wood essential oils of C. libani, C. atlantica and C. deodara inhibited the proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Atlas cedarwood is typically very rich in sesquiterpenes (primarily himachalenes) and frequently used in aromatherapy for nervous disorders like anxiety and stress. Research shows that Atlas cedarwood possesses analgesic, antiinflammatory,anti-leukemic, and insecticidal properties [67][68][69][70].…”
Section: Atlas Cedarwood (Cedrus Atlantica) Essential Oilmentioning
confidence: 99%
“…Atlas cedarwood is typically very rich in sesquiterpenes (primarily himachalenes) and frequently used in aromatherapy for nervous disorders like anxiety and stress. Research shows that Atlas cedarwood possesses analgesic, antiinflammatory,anti-leukemic, and insecticidal properties [67][68][69][70].…”
Section: Atlas Cedarwood (Cedrus Atlantica) Essential Oilmentioning
confidence: 99%
“…Cedrus atlantica (CAt) was introduced to Europe and the U.S.A in the mid-19th century and has been used in forestation and tree planting operations [21]. Previous studies have reported that CAt extracts reduce postoperative pain and inhibit the growth of K562 leukemia cells [22,23], although the exact regulatory molecules in CAt extract with anti-cancer have yet to be completely elucidated.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…The results suggest that wood essential oil of the three species of Cedrus is potent source of active principles required for the production of anticancer drugs. [41] Flavonoids extracted and purified from needles of C. deodara were tested for antitumor activity. It was observed that the total flavonoid content of the needle of C. deodara reached up to 54.28% in which quantities of major ingredients, namely myricetin, quercetin, kaempferol, and isorhamnetin were 1.89, 2.01, 2.94, and 1.22 mg/g, respectively.…”
Section: Antiapoptotic Activitymentioning
confidence: 99%